Her Dark Wings - Salisbury, Melinda (New York Delacorte Press, 2023)
"The great love of Corey's life has always been her best friend, Bree: closer than sisters, their bond is unbreakable. Or so Corey thought, until Bree betrays her in the worst way possible. When Bree's sudden death rocks their small island community, Corey is heartbroken and furious. How can she mourn her one-time friend when she is still so angry at her? But though Bree has passed on, her spirit remains--and her and Corey's tale isn't finished yet. Soon, Corey finds herself called to the Underworld, where she'll encounter creatures of legend, including the terrifying, beautiful Furies, who encourage her to embrace her rage. And then there is Hades himself: a god who is unyielding, cold and irritatingly arrogant. Her time in Hades's realm will change her, because the more she learns about herself, the more Corey's own power stirs. But can she resist the lure of the darkness within?"--
Coping with the sudden death of her ex-best friend, eighteen-year-old Corey finds herself plunged into the Underworld, where she must contend with mythical beasts, her own burgeoning powers, and the arrogant, handsome Lord of the Dead.
Ages 14+
112701
Keywords: Emotions -- Juvenile fiction; Voyages to the otherworld -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Emotions -- Fiction; Fantasy; Fantasy fiction; Mythological fiction; Novels; Romance fiction